Dynamic Behavior of a Railway Wheelset on a Roller Rig versus Tangent Track - N. Bosso; A. Gugliotta; A. Somà (Shock and Vibration)
This paper addresses the comparison of dynamic behavior of a wheelset on roller and on rails. The development of equations of kinematics and motion allow to put in evidence the intrinsic differences between the dynamic behavior on rail and on roller. The stylized conical profile approximation of the wheel allows to focus the attention on the differences in creepages definition and in contact point shift due to the roller curvature. The treatise is addressed to a full scale roller and can be extended in the case of scaled roller rig to be applied in the case of the test bench developed for experimental analysis. In the present paper numerical simulation and examples are used to proof the analytical results.